Literasi Informasi Melawan Hoaks Bidang Kesehatan di Komunitas Online - Christiany Juditha (FISIP Universitas Atma Jaya Yogyakarta, 2019)
This study aims to describe the development of information literacy in online communities to fight hoaxes in the health sector. The research method used is qualitative content analysis. The results show the seven pillars of information literacy, which are identification, coverage, planning, information gathering, evaluation, management and presentation of information are built into the Indonesian Hoaxes group. Anyone can participate by asking questions, discussing, and clarifying hoaxes in online media. Administrator and community members have the same role to give each other information literacy so that they get the same understanding of the truth information.